2022
DOI: 10.1021/acs.macromol.2c01196
|View full text |Cite
|
Sign up to set email alerts
|

User Guide to Ring-Opening Metathesis Polymerization of endo-Norbornene Monomers with Chelated Initiators

Abstract: The development of facile synthetic strategies to access well-defined polymers promises to provide advanced soft materials with functionality that rivals that observed from nature. To this end, ring-opening metathesis polymerization (ROMP) presents a compositionally simple and rapid strategy for controlled polymerization, yet it has received far less attention relative to radical counterparts. This limited attention arises in part from scattered reports on optimization strategies and a narrow monomer scope. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…We observed that the reaction purged with air has a slightly higher M n compared with the ones purged under nitrogen and vacuum; however, the difference is not statistically significant (Figure S4). The high tolerance to oxygen when initiator ligands are used during ROMP was also recently observed . Moreover, we suspect the slightly higher M n is caused by small amounts of oxygen in the monomer that can degrade the initiator during the reaction.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…We observed that the reaction purged with air has a slightly higher M n compared with the ones purged under nitrogen and vacuum; however, the difference is not statistically significant (Figure S4). The high tolerance to oxygen when initiator ligands are used during ROMP was also recently observed . Moreover, we suspect the slightly higher M n is caused by small amounts of oxygen in the monomer that can degrade the initiator during the reaction.…”
Section: Resultssupporting
confidence: 68%
“…However, access to linear polymers with degree of polymerizations ( DPs ) higher than 1000 and low dispersity ( Đ ) remains a challenge, as seen in Figure . The synthesis of high polymers with low Đ via ROMP are mostly performed under an inert atmosphere with reaction times that can exceed several hours (depending on the catalyst). , …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the first initiated polymers have longer synthesis times at a higher monomer concentration, compared to the last initiated polymers in the vial. The narrow standard deviation in Đ for A n indicates precise and reproducible syntheses when using the ASM, however, the polymers exhibit a larger Đ than found in literature ( Đ = 1.16–1.30 for similar synthesis using G3 37 ). Since the Đ of the manual ROMP (1.4) is comparable to those of the machine, the larger dispersities can be ascribed to the synthesis procedure or the GPC.…”
Section: Resultsmentioning
confidence: 62%
“…In order to accurately measure the forward rate of the metathesis reaction: ring opening of cyclohexene by cyclohexylidene 1 -Ru, triphenylphosphine PPh 3 , a strong σ-donating, labile ligand that is inexpensive and easy to handle, was added to the reaction mixture. We anticipated that PPh 3 will bind to the Ru center , of 1 - 2 -Ru and form a more stable PPh 3 ligated complex ( 1-2 -Ru­(PPh 3 )), thus suppressing the reverse ring closing reaction (Figure ). When 10 equiv of PPh 3 was added to the reaction mixture, the rate of formation of 1 - 2 -Ru­(PPh 3 ) increased significantly, consistent with suppression of the reverse reaction.…”
Section: Resultsmentioning
confidence: 99%